Atividade social em aulas de língua inglesa : experiência unplugged em uma escola da rede pública estadual de Sergipe - Soares, Nadja Maria Santos (2020)
This research aims at analyzing the contributions of Social Activity in English classes, in an unplugged perspective, for the development of students. The unplugged activities have been adopted in view of the need to adapt the teaching and learning of English language to the reality of Internet access for both students and the school which is the context of the study. The theoretical framework outlined starts from the Theory of Socio-Historical-Cultural Activity (VYGOTSKY, 2001; LEONTIEV, 1977; ENGESTRÖM, 1999; HOLZMAN, 2009); going through Social Activities in foreign language classes (LIBERALI, 2009,2012). The study was developed from a project with Social Activities in English, with a group of students from the three last grades of formal basic education in Brazil: high school, in a public school in the state of Sergipe. The methodological perspective is the Critical Collaboration Research (MAGALHÃES, 2006; MAGALHÃES and FIDALGO, 2011, 2019), which allows knowledge construction, creation, and recreation of new possibilities of work and establishes learning as a way of transformation, better participation, and coexistence in society – in this research, specifically, within the scope of digital cultures. Data were collected through a questionnaire, teaching logs, chat circles and analyzed according to the perspective of the Teaching Research (FREEMAN, 1998). The analysis and interpretation of the data indicate results that establish a dialectical relationship between teaching and learning English and the student's life, so that he can recognize, reflect and analyze the contents developed throughout the project and use them in real communication contexts and digital literacy practices, thus breaking with an education of bureaucratic bias and that does not promote learning that excels in relating the knowledge built at school with human development and its possibilities for future action in society.